Probing Undergraduate EFL Students’ Motivation to Teach as Career Decision Making: A Narrative Inquiry - Arya Prabawa; Dewi Rochsantiningsih; Nur Arifah Drajati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The teacher shortage has increased in the last couple of years, and the teacher profession has become less attractive to students. This phenomenon can be seen from the contrasting data comparison between the number of students entering education majors against the increasing number of teachers needs in 2022-2024. To understand college students’ motivation to teach, this study intends to uncover what motivates English Foreign Language (EFL) students to make career choices towards the teaching profession and what EFL students’ plans are after completing their studies. Utilizing a narrative inquiry, the data were collected from four students through written narratives and semi-structured interviews at a private university in Indonesia. Based on the findings, one student wants to become a teacher as their first choice, with plans to find a teaching job. Another two students decided to become teachers as their second choice; both have their ideas about the teaching profession, with one planning to commit to another profession, while the other is looking at the situation. The last student does not want to become a teacher because of internal and external influences, planning to look for another profession as his choice. This makes it necessary to take action on how the teacher preparation program needs to evaluate, and the government needs to make the teaching profession more appealing to undergraduate EFL students.